PENGARUH KONTEN AKUN INSTAGRAM @JKTINFO TERHADAP PEMENUHAN KEBUTUHAN INFORMASI LALU LINTAS FOLLOWERS: (Survei Terhadap Followers Akun Instagram @jktinfo) - Arshinta Eka Putri, (2020)
@jktinfo is an Instagram account that spread information about the city of Jakarta and surrounding areas. The most widely disseminated information is about Jakarta's traffic conditions. Information uploaded as content are photos, videos and captions. This study aims to determine how much influence the @jktinfo Instagram account content has on fulfilling followers' information needs. The theory uses of this study is Uses and Gratification. The concept in this study include citizen journalism, social media, Instagram, content, photos, videos, captions, information needs and traffic. The research method used in this study is quantitative. The sampling technique uses random sampling and the study population is followers of the Instagram account @jktinfo, with a total sample of 100 results from the Taro Yamane formula. The results of the coefficient of determination test in this study showed that 49.2% of the traffic information needs of followers is influenced by the content of the Instagram account @jktinfo, while the remaining 51.8% is influenced by other factors not examined. Hypothesis test results show that the content of the Instagram account @jktinfo has a significant effect on meeting the information needs of its followers. Keyword: Instagram, Information Needs, Content, Traffic, Social Media.